Development of nanocomposite with epoxidized natural rubber and functionalized multiwalled carbon nanotubes for enhanced thermal conductivity and gas barrier property. (15th October 2015) - Jo, Jae Ok; Saha, Prosenjit; Kim, Nam Gyeong; Chang Ho, Choi; Kim, Jin Kuk
Graphical abstract: Highlights: Multiwalled CNTs have been functionalized by aminosilane and TiO2 . Nanocomposites manufactured with functionalized CNTs and epoxidized natural rubber. Nanocomposite showed enhanced thermal conductivity and gas barrier ability. The mechanism is proposed and established by extensive characterization. Epoxidation of natural rubber was found to be a major factor for improvement. Abstract: Multiwalled pristine carbon nanotubes (mwCNTs) were treated with conventional mixed acid to functionalize outer surface of nanotubes with two unique chemical approaches using aminosilane solution and TiO2 dispersion. Pristine and functionalized mwCNTs were dispersed subsequently in matrices of natural rubber (NR)–chlorobutyl rubber (CIIR) and epoxidized natural rubber (ENR)–CIIR to prepare nanocomposites by simple and eco-friendly melt blending method. The effect of surface treatment of mwCNTs, and epoxidation of NR on the composite properties was evaluated for thermal conductivity and gas barrier property. Nanocomposites prepared with surface functionalized mwCNTs and epoxidized NR were found to exhibit greater thermal conductivity and excellent gas barrier properties compared to pristine mwCNT reinforced CIIR–NR nanocomposites. A maximum thermal conductivity was observed for nanocomposite obtained from 20% ENR and 3% (by weight) mwCNTs functionalized with aminosilane. While a maximum gas barrier property was exhibited by nanocomposite with 20% ENR and 3% (by weight) mwCNTs treated with TiO2 . Results indicate that the presence of epoxy moieties of ENR provided a stronger network formation between aminosilane treated mwCNT surface and rubber matrices to exhibit higher thermal conductivity and metal oxide particles adhered to TiO2 treated mwCNTs found to impart maximum resistance in transfer of oxygen gaseous molecules nanocomposite.